Μοριακή ταυτοποίηση επιφυτικών ζυμών αμπέλου και αξιολόγηση τους ως ανταγωνιστικοί παράγοντες κατά των μυκήτων του γένους Aspergillus Άθροισμα Nigri - Χρίστου, Ουρανία (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2012)
The aim of this study was the molecular identification of phyllosphere grapevine yeasts and their evaluation as biological agents against Aspergillus section Nigri. Initially, grapevine yeasts were isolated from the grape varieties Maratheftiko and Cabernet Sauvignon from 4 regions of Limassol· Koilani, Agios Ambrosios, Pachna and Arsos. The yeast isolates were studied macroscopically and microscopically. Genomic DNA was isolated from each yeast sample and used for the amplification and sequencing of the D2 region of the nuclear large-subunit (LSU) ribosomal RNA gene. The DNA sequence of the gene for each isolate was then determined through the process of capillary electrophoresis on an Applied Biosystems genetic analyzer. The sequences were compared to a MicroSeq® Fungal Gene library that contains D2 sequence entries from more than 1000 validated species, using MicroSeq® ID Analysis software. Moreover, the sequences obtained were compared to the database of NCBI using the BLAST algorithm. After the molecular identification of the yeasts the isolates were evaluated in vitro as biological agents against black Aspergilli. For this purpose, two different sets of experiments were performed. All of the yeast isolates were screened for in vitro antagonism against A. tubingensis by the dual culture technique on Petri dishes containing Yeat Malt Agar medium. The antagonistic effects were recorded by measuring the percentage inhibition of the radial growth of A. tubingensis, and the width of any inhibition growth. The yeasts that were able to inhibit the growth of the pathogen were selected for the following experiments. A collection of 34 yeast isolates was used for the evaluation of their antagonistic activity against A. tubingensis in a detached berry test. Berries from bunches of Red Globe variety were immersed in a suspension of the selected yeast isolates and 24 hours later, a calibrated wound was made with a sterile needle on each berry. The wound was spot-inoculated with a conidial suspension of A. tubingensis. The percentage of fungal growth inhibition was determined for each yeast isolate. The activity of the two most efficient yeast isolates in the laboratory screening experiments (Aureobasidium pullulans) was compared to the activity of the commercial fungicides Geoxe (fludioxonil 50%), Chorus (cyprodinil 50%) and Switch (cyprodinil 37.5% and fludioxonil 25%) under field conditions in two different wine-producing regions of Limassol (Pachna, Maratheftiko vineyard˙ Agios Amvrosios, Cabernet sauvignon vineyard). The results showed that the yeasts that were applied in the fields did not reduce infection of grape berries with black Aspergilli since the frequency of the infected berries was not significantly different compared to the control plants.
Keywords: Vineyards; Fungi; Αμπελώνες; Μύκητες